A unified framework of high order structure-preserving B-splines Galerkin methods for coupled nonlinear Schrödinger systems. (15th November 2021) - Castillo, Paul; Gómez, Sergio
Abstract: Using a general computational framework, we derive an optimal error estimate in the L 2 norm for a semi discrete method based on high order B-splines Galerkin spatial discretizations, applied to a coupled nonlinear Schrödinger system with cubic nonlinearity. A fully discrete method based on a conservative nonlinear splitting Crank-Nicolson time step is then proposed; and conservation of the mass and the energy is theoretically proven. To validate its accuracy in space and time, and its conservation properties, several numerical experiments are carried out with B-splines up to order 7.